The Employment and Income Effects of Eight Chronic and Acute Health Conditions - Sylvia Dixon (New Zealand Government, The Treasury, 2015)
This paper examines the impact of eight different health conditions on the employment rates and incomes of working-aged New Zealanders who develop them. The conditions studied are stroke, traumatic brain injury, coronary heart disease, diabetes, chronic obstructive pulmonary disease (COPD), breast cancer, melanoma, and prostate cancer. The paper focuses on 20-59 year olds who were in wage or salaried employment at the time they were first diagnosed with the condition, and survived for at least four years post- diagnosis. Using administrative data from the Integrated Data Infrastructure (IDI), it estimates the impacts that the illness or injury had on their employment, income support, earnings and regular personal incomes, over the following four years. Impacts are estimated by comparing the post-diagnosis employment and incomes of those who developed the condition with those of matched comparison groups. We find evidence of significant employment rate reductions, income support increases, and income losses in the four years after first diagnosis for six of the eight conditions (stroke, traumatic brain injury, coronary heart disease, diabetes, COPD and breast cancer). After four years, the estimated negative impacts on the proportion who were employed ranged from 2.6 percentage points (for diabetes) to 19 percentage points (for stroke). The estimated negative impacts on monthly personal incomes ranged from 3% (for COPD) to 15% (for stroke). The employment and income impacts of traumatic brain injury, coronary heart disease, diabetes and breast cancer decreased in size during the four years after diagnosis, but remained significant. There was little improvement in the average employment and income effects of stroke during the four-year follow-up period. In the case of COPD, an initially very small impact on employment and incomes grew gradually larger.
Keywords: I1; 330; Gesundheit; Chronische Krankheit; Erwerbstätigkeit; Haushaltseinkommen; Neuseeland